(untitled) - Minasi, Mark (Indianapolis, Indiana, 2006)
The In-depth Coverage You've Been Waiting for on SP1 and R2 Picking up where Mastering Windows Server 2003 left off, bestselling author and leadingWindows Server expert Mark Minasi returns with a much-anticipated Upgrade Edition that delivers exactly the information you need to understand SP1 and R2.
Keywords: Microsoft Windows server,Computer networks,Microsoft Windows server,Mạng máy tính